(untitled) (Global Journal of Science Frontier Research, 2013)
During the past half century, the Punjab State achieved exemplary growth in food-grain production. The fast shift in area from traditional diversified crops to monoculture of rice-wheat system was driven by forces such as price policy, technological change, market infrastructure and low cost of irrigation. But due to over exploitation of water resource, the sustainability of existing crop systems is becoming doubtful, creating critical second generation problem. This requires separate treatments in three distinct agro-climatic regions of the state. The semi-hilly tracts, comprising about 10% area, requires check dams against fast water run-off, cultivation across the slope and crops using less water such as maize, groundnut, pulses etc. The potential cotton belt, forming one-fourth area, has brackish groundwater which needs to be used in conjunction with canal water; and the paddy crop in the area should be strictly discouraged. The fast receding water table in the central food security belt of the country is attributed to spreading rice cultivation. This demands policies of suitable water pricing; setting up tension-meters to monitor water requirements; laser leveling fields; keeping plot size smaller; genetic improvement of rice by developing short duration and late sown varieties; direct seeding of rice; encouraging sprinkler and drip irrigation; mulching with abundant quantities of crop residues and various other such agronomic practices.